2019
DOI: 10.1519/jsc.0000000000003021
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass and Femur Length Are Inversely Related to Repetitions Performed in the Back Squat in Well-Trained Lifters

Abstract: Cooke, DM, Haischer, MH, Carzoli, JP, Bazyler, CD, Johnson, TK, Varieur, R, Zoeller, RF, Whitehurst, M, and Zourdos, MC. Body mass and femur length are inversely related to repetitions performed in the back squat in well-trained lifters. J Strength Cond Res 33(3): 890–895, 2019—The purpose of this research note was to examine whether relationships existed between anthropometrics (body mass, body fat percentage [BF%], and femur length) and descriptive characteristics (age and sex) with repetitions performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 7 publications
0
20
1
Order By: Relevance
“…s −1 was 2–11, 4–19, and 4–24 repetitions, respectively [ 115 ]. Therefore, due to the extensive range in repetitions that can be performed at each percentage of 1RM [ 7 , 8 ] and at each velocity loss threshold [ 115 ], as well as the FRV [ 116 ], the ACV corresponding to a specific RPE [ 13 ], and the individualized velocity decay, each individual will experience varying degrees of fatigue, terminate each set at a different proximity to failure, and perform a different number of repetitions and magnitude of relative volume. Conclusively, an autoregulatory model conceptualizing the overarching results from this meta-analysis may be required to suggest avenues for future research and potential practical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…s −1 was 2–11, 4–19, and 4–24 repetitions, respectively [ 115 ]. Therefore, due to the extensive range in repetitions that can be performed at each percentage of 1RM [ 7 , 8 ] and at each velocity loss threshold [ 115 ], as well as the FRV [ 116 ], the ACV corresponding to a specific RPE [ 13 ], and the individualized velocity decay, each individual will experience varying degrees of fatigue, terminate each set at a different proximity to failure, and perform a different number of repetitions and magnitude of relative volume. Conclusively, an autoregulatory model conceptualizing the overarching results from this meta-analysis may be required to suggest avenues for future research and potential practical applications.…”
Section: Discussionmentioning
confidence: 99%
“…PBT also involves prescribing load based on a single 1RM testing session; thus, if abnormal performance or improper administration were present, the training stimulus applied for the study intervention or successive training cycle may be inappropriate for the intended outcome and may impact other variables (i.e., fatigue, load, volume) in the prescription [ 5 ]. Finally, repetitions performed at given intensities are largely lift-specific [ 7 ] and highly variable between individuals [ 8 ]; therefore, PBT fails to accurately quantify proximity to failure and the degree of neuromuscular fatigue for each individual and lift.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in lieu of prescribing 4 sets of 8 repetitions at 70% of one-repetition maximum (1RM), practitioners may prescribe 4 sets at 70% of 1RM of as many repetitions as possible until ACV falls below 80% of the first repetition’s ACV. This autoregulation of the training volume avoids using a predetermined number of repetitions since there is large inter-individual variation in the number of repetitions that can be performed during barbell exercises at the same relative intensity ( Cooke et al, 2019 ; Shimano et al, 2006 ). Indeed, to date, two studies have demonstrated greater strength gains when using VBT versus percentage-based training over the long-term ( Dorrell et al, 2020 ; Orange et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite 1-RM is still the standard for dynamic maximal strength assessment [2,4], prescribing strength exercise using the same % of 1-RM can yield different intensities in different individuals. Indeed, there is high interindividual variability in the number of repetitions performed to failure at the same % of 1-RM [5,6]. Consequently, other methods [7] have been proposed to prescribe resistance exercise intensity using a load that allows performing the desired number of repetitions at maximum before failure (multiple-RM) or one that produces a certain rate of perceived exertion (RPE).…”
Section: Introductionmentioning
confidence: 99%